Estimation of parameters of the scattered signals spectra in the radar of vertical sounding of at-mosphere - Олейников, В.Н.; Дорошенко, С.В.; Пшеничный, В.Д. (Radiotekhnika, 2017)
Features of methods for estimating parameters of scattered signals in radar stations of vertical atmospheric sounding are considered. Based on the experimental results of sounding the atmosphere, a model of the scattered signals is proposed. Estimation of the accuracy of the wind speed measurement, obtained by various methods of spectra parametrization, is investigated using imitation modeling. Methods are proposed for reducing the shift in estimates of the moments of the spectrum of the scattered signal power due to reflections from the earth's surface and edge effects in the parametrization of the spectra.